Physical and chemical properties of rice varieties grown in Mekong delta - Lai, Dat Quoc; Ngo, Thanh An; Nguyen, Quang Long; Nguyen, Hoang Dung; Pham, Duy Tien (Vietnam Journal of Science and Technology, 2022)
125 rice samples of 10 rice varieties (Daithom8, IR50404, Jasmine85, DS1, OM4900, OM5451, OM6976, OM7347, ML202, Glutinous rice) collected from 10 provinces in the Mekong Delta were not different in grain length ranging from medium to long and were mainly tapered in shape. Except for DS1, because of the Japonica variety, it is round in shape. Their chemical ingredients slightly differed between varieties, but there was a clear difference in amylose content, according to which these rice samples were divided into 4 groups: samples with very low amylose content ranging from 3 to 9 %, accounting for 3 % of the total samples and belonging to the Glutinous rice variety; samples with medium amylose content (20 - 25 %), accounting for 29 % of the total samples and mainly belonging to varieties Jasmine85 and OM5451; samples with high amylose content (≥ 25 %), accounting for 20 % of the total samples and belonging to varieties IR50404, ML202, and OM6976; and samples with low amylose content (9 - 20 %), accounting for 48 % of the total samples and belonging to the remaining varieties. Based on physical and chemical properties, the rice varieties of 125 survey samples were classified into 3 groups with specific characteristics. In group 1, samples were characterized by particle size, particle shape, moisture, lipid and ash content; in group 2, samples were characterized by properties such as starch and amylose content; group 3 was characterized by width, protein and amylopectin. In addition, rice samples were divided into 3 groups based on growing location and physicochemical properties.